Environmental science and technology : - Spellman, Frank R. (Government Institutes, 1999)
Designed for both professional and student use, this text serves as an introduction to environmental science and technology and provides clear explanations and illustrations of the interconnection between the basics (concepts) and their actual use (applications). Because the authors wrote for readers with little or no science background, the text contains straightforward, jargon-free language